A project to constrain emission from giant gaseous shells around high redshift radio galaxies - Moyano, Martín Manuel (2015)
Fil: Moyano, Martín Manuel. Universidad Nacional de Córdoba. Observatorio Astronómico de Córdoba; Argentina.